Baroreflex responses to activity at different temperatures in the South American rattlesnake, Crotalus durissus - Filogonio, Renato [UNESP]; Neto, Antônio V. G. S.; Zamponi, Mariana M.; Abe, Augusto S. [UNESP]; Leite, Cléo A. C. (Springer Nature, 2021)
In humans, physical exercise imposes narrower limits for the heart rate (fH) response of the baroreflex, and vascular modulation becomes largely responsible for arterial pressure regulation. In undisturbed reptiles, the baroreflex-related fH alterations at the operating point (Gop) decreases at elevated body temperatures (Tb) and the vascular regulation changes accordingly. We investigated how the baroreflex of rattlesnakes, Crotalus durissus, is regulated during an activity at different Tb, expecting that activity would reduce the capacity of the cardiac baroreflex neural pathway to buffer arterial pressure fluctuations while being compensated by the vascular neural pathway regulation. Snakes were catheterized for blood pressure assessment at three different Tb: 15, 20 and 30 °C. Data were collected before and after activity at each Tb. Baroreflex gain (Gop) was assessed with the sequence method; the vascular limb, with the time constant of pressure decay (τ), using the two-element Windkessel equation. Both Gop and τ reduced when Tb increased. Activity also reduced Gop and τ in all Tb. The relationship between τ and pulse interval (τ/PI) was unaffected by the temperature at resting snakes, albeit it reduced after activity at 20 °C and 30 °C. The unchanged τ/PI and normalized Gop at different Tb indicated those variables are actively adjusted to work at different fH and pressure conditions at rest. Our data suggest that during activity, the baroreflex-related fH response is attenuated and hypertension is buffered by a disproportional increase in the rate which pressure decays during diastole. This compensation seems especially important at higher Tb where Gop is already low.
Keywords: Baroreflex effectiveness index; Oscillatory power fraction; Sequence method; Time constant of pressure decay; Windkessel